Digest: Great tits and their ticks: Life‐history traits affect tick fitness. (5th July 2022) - Matson, Kevin D.; de Boer, Willem F.; Ottenburghs, Jente
Abstract: Ectoparasites such as ticks face many challenges to reproduce. They must maximize the size of their blood meal while avoiding being removed by their host. In a new study, Fracasso and colleagues followed the fate of individual ticks to determine which life‐history traits impact tick fitness. Their findings reveal a complex interplay between numerous parameters, including feeding time and engorgement weight. The situation is likely even more complicated when considering vector‐borne pathogens.